Efektivitas Senam Kreasi Melalui Video Pada Aspek Perkembangan Motorik Kasar Anak 5-6 Tahun di TKN Pembina Syamtalira Bayu - Syurfil Rahmi; Yusnaini; Mutia Sari (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study focuses on the effectiveness of creative gymnastics through video on the gross motor development of 5-6 year old children at Syamtalira Bayu State Kindergarten. This study aims to determine the effectiveness of creative gymnastics through video media on the development of gross motor skills of 5-6 year old children. This study uses a qualitative approach with a descriptive research type. The sample in this study amounted to 18 children aged 5-6 years and the informants in this study were three class teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that creative gymnastics through video proved effective in supporting the gross motor development of 5-6 year old children. Children showed high enthusiasm in participating in the activities, were able to imitate most of the gymnastics movements shown, and experienced a gradual increase in coordination, balance, agility, and large muscle strength. It also increased children's focus and participation, and made it easier for them to understand the movements through repetition.